RUSSIAN NATIONAL CONGRESS OF CARDIOLOGISTS AND CONGRESS OF CARDIOLOGISTS OF CIS STATES (Столичная издательская компания, 2015)
Russian National Congress of cardiologists and Congress of cardiologists of CIS States.